2021
DOI: 10.1021/acs.bioconjchem.0c00691
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigations, Cellular Imaging, and Radiolabeling of Neutral, Polycationic, and Polyanionic Functional Metalloporphyrin Conjugates

Abstract: Over the past decade, porphyrin derivatives have emerged as invaluable synthetic building blocks and theranostic kits for the delivery of cellular fluorescence imaging and photodynamic therapy. Tetraphenylporphyrin (TPP), its metal complexes, and related derivatives have been investigated for their use as dyes in histology and as components of multimodal imaging probes. The photophysical properties of porphyrin–metal complexes featuring radiometals have been a focus of our attention for the realization of fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
(110 reference statements)
0
9
0
Order By: Relevance
“…In prostate cancer, their expression rates are in the range between 63–100% ( Beer et al, 2012 ) and moreover, they upregulate promoters of angiogenesis, essential for the metastasis of the cancerous cells ( Elshafae et al, 2016 ). In recent years, GRPRs have increasingly received a lot of interest for being targeted to treat and image prostate cancer ( Ciaffaglione et al, 2021 ). These receptors have shown a high affinity to two natural peptides: GRP consists of 27 amino acids, found in mammals, which is homologous to the amphibian bombesin (BBN) peptide from the species Bombina ( Anastasi et al, 1971 ; Spindel, 1986 ; Lee et al, 1994 ), a 14 amino acids chain ( Schroeder et al, 2011 ; Beer et al, 2012 ).…”
Section: Molecular Imaging Approaches To Drug Discovery Processesmentioning
confidence: 99%
“…In prostate cancer, their expression rates are in the range between 63–100% ( Beer et al, 2012 ) and moreover, they upregulate promoters of angiogenesis, essential for the metastasis of the cancerous cells ( Elshafae et al, 2016 ). In recent years, GRPRs have increasingly received a lot of interest for being targeted to treat and image prostate cancer ( Ciaffaglione et al, 2021 ). These receptors have shown a high affinity to two natural peptides: GRP consists of 27 amino acids, found in mammals, which is homologous to the amphibian bombesin (BBN) peptide from the species Bombina ( Anastasi et al, 1971 ; Spindel, 1986 ; Lee et al, 1994 ), a 14 amino acids chain ( Schroeder et al, 2011 ; Beer et al, 2012 ).…”
Section: Molecular Imaging Approaches To Drug Discovery Processesmentioning
confidence: 99%
“…An extended study of neutral, polycationic, and polyanionic metalloporphyrins labeled with 68 Ga showed extremal flexibility for modifications of the porphyrin cores [ 84 ]. The addition of nitroimidazole or sulfonamide groups, which were used as vectors, improved the pharmacokinetics of porphyrin tags and the stability in serum.…”
Section: Porphyrins As Ligands For Radiometalsmentioning
confidence: 99%
“…Hence, a likely cause for the poor uptake many be due to low solubility of the compound ( inter alia , as a result of the long aliphatic linker). ( Ciaffaglione et al, 2021 ).…”
Section: Porphyrin-peptide Conjugatesmentioning
confidence: 99%
“…The reaction between amines on peptides and activated carboxylic acids on porphyrin derivatives have been extensively investigated ( Tomé et al, 2004 ; Gabriel et al, 2007 ; Giuntini et al, 2011 ; Shi et al, 2011 ; Dosselli et al, 2013 ; Orosz et al, 2013 ; Li et al, 2015 ; Jiang et al, 2016 ; Chen et al, 2018 ; Liu et al, 2018 ; Ciaffaglione et al, 2021 ). For example, in 2011, Mező et al conjugated one and two tetrapeptides to tri-cationic meso -tri (4-N-methylpyridyl)-mono- (4-carboxyphenyl) porphyrin (TMPCP) and bi-cationic meso -5,10-bis(4-N-methylpyridyl)-15,20-di- (4-carboxyphenyl)porphyrin (BMPCP) respectively.…”
Section: Porphyrin-peptide Conjugatesmentioning
confidence: 99%